Physical and Social Environmental Conditions Affected by Rob Flood on the Semarang Coast - Deka Setiawan; Dewi Liesnoor Setyowati; Hamdan Tri Atmaja; Moh. Solehatul Mustofa (Universitas Negeri Semarang, 2022)
Flood is an environmental problem that regularly occurs in communities around the coast. This condition causes changes in the physical and social environment of the community so that they can continue to live with the requirements of the tidal flood environment. Communities on the coast must adjust to the conditions in which they live in tidal flood areas. This study aims to find out how the physical and social environmental conditions of the community affected by the tidal flood on the coast of Semarang are and the factors that affect the physical and social needs of the community affected by the tidal flood on the coast of Semarang. This study uses a qualitative method. Data were collected by observing the field, conducting interviews with informants, and studying documents or literature. The location of this research is in Kaligawe and Tambak Lorok Villages, Semarang. The results of this study are that the Kaligawe and Tambak Lorok communities affected by tidal flooding on the coast of Semarang adapt to the physical environment, namely the conditions of their homes, places of worship, and public facilities. House building because the house building is lower than the village road. In the social environment of the community affected by tidal flooding both in Kaligawe and Tambak Lorok, there is a kind of bond that makes the community strong in facing tidal flooding for dozens or even decades. The internal factor is the feeling of sharing the same fate, making them strengthen each other outwardly and inwardly.